STRATEGI MILITER ART OF WAR PADA PROSES INTERNASIONALISASI PT INDOFOOD CBP DI AFRIKA - Fadchurrozi, Imam (Indonesian Association for International Relations, 2025)
This study aims to analyze the application of Sun Tzu’s Art of War principles in PT Indofood CBP’s internationalization strategy in Africa. A qualitative approach with descriptive analysis is employed, utilizing the OLI Paradigm (Ownership, Location, Internalization) as an analytical framework to examine factors influencing Indofood’s expansion. Sun Tzu’s principles, such as knowing oneself and the competition, flexibility, and strategic alliances, are analyzed alongside Indofood’s ownership advantages in technology and production (O), the attractiveness of investment locations in Africa (L), and internalization strategies to maintain control over supply chains and distribution (I). The findings indicate that Indofood adapts its products to local preferences and establishes strategic partnerships, including social initiatives such as polio vaccination programs, to strengthen market penetration. This study concludes that integrating Sun Tzu’s military strategies with the OLI Paradigm offers valuable insights for companies navigating complex and competitive global markets.